Strengthening of a traditional territorial tenure system through protagonism in monitoring activities by lobster fishermen from Juan Fernández Islands (Chile) - Ernst, Billy (2010)
A small-scale rock lobster [Jasus frontalis (Milne-Edwards, 1837)] fishery has operated for decades in the Juan Fernández Archipelago (Chile) under a traditional territorial tenure system that has put an effective cap on the size of the fishing force. Research on this fishery started in the mid 1960s, but time series of basic indicators other than annual landings have not been collected on a regular basis. Scientific input to the central administration has consisted of sporadic monitoring and assessments, the latter consisting of equilibrium models supporting totalallowable-catch recommendations, but introduction of such a system in the tightly structured but informal management system could have undesirable effects for both the social and biological sectors of the fishery. Seeing the need for improved advice, the local fishermen’s organization (“syndicate”) acted to develop its own spatially explicit indicators of stock status and fishery performance, which could be made available to the fisheries authority and used in fostering strategies compatible with the informal but effective management system. A collaborative effort between the syndicate and independent scientists led to the design and implementation of a cost-effective logbook-sampling program. Under this bottom-up arrangement data are shared voluntarily by individual fishermen and compiled with assistance from the syndicate. The spatially explicit information collected is used to compute and standardize a robust and precise index of relative abundance. This case is discussed in the context of the “barefoot ecologist” model for the provision of scientific support to the management of small-scale fisheries.